Caracterização das habilidades do processamento auditivo em crianças com desnutrição - Caldas, Patrícia Andréia [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The damage caused by malnutrition on child development are not yet fully known. The high prevalence of malnutrition and possible impairments in physical, intellectual and, or language leads us to reflect on how auditory information is processed by malnourished children. The aim of this study was to characterize and compare the performance of malnourished children and normal children in auditory processing. The sample comprised 30 children belonging to the age group of five to ten years, of both genders, with 15 malnourished children comprised the sample group and 15 children with adequate nutritional status, as a control group. The groups were paired according to gender, age and grade level. Both groups underwent peripheral and central auditory assessment, noted that malnourished children had lower performance in the ability of auditory memory for verbal and nonverbal sounds compared with the control group, the same occurred in closing skills and background figure. Malnourished children also had low performance on the physiological mechanism of selective attention processes and gnosis decoding, encoding and organization when compared with normal children. Therefore it is concluded that malnutrition affects the development of the central auditory processes.

Os prejuízos causados pela desnutrição no desenvolvimento infantil não são ainda totalmente conhecidos. A elevada prevalência da desnutrição e os possíveis comprometimentos no desenvolvimento físico, intelectual e/ou de linguagem nos leva a refletir sobre como as informações auditivas são processadas por crianças desnutridas. Assim, o objetivo deste estudo foi caracterizar e comparar o desempenho de crianças com desnutrição e crianças eutróficas nas habilidades do processamento auditivo. A amostra foi composta por 30 crianças pertencentes a faixa etária de cinco a dez anos, de ambos os gêneros, sendo 15 crianças com desnutrição que compuseram o grupo amostral e 15 crianças, com estado nutricional adequado, como grupo controle. Os grupos foram pareados segundo gênero, faixa etária e escolaridade. Ambos os grupos foram submetidos à avaliação auditiva periférica e central, pode-se observar que crianças desnutridas apresentaram desempenho inferior na habilidade de memória auditiva para sons verbais e não verbais quando comparadas com o grupo controle, o mesmo ocorreu nas habilidades de fechamento e figura fundo. As crianças desnutridas também tiveram baixo desempenho no mecanismo fisiológico de atenção seletiva e nos processos gnósicos de decodificação, codificação e organização, quando comparadas com as crianças eutróficas. Sendo assim conclui-se que a desnutrição afeta o desenvolvimento dos processos auditivos centrais.
Keywords: Desnutrição; Fonoaudiologia; Percepção auditiva - Distúrbios; Auditory perception in children